Mysteriosos Demystified: Topical Strategies Within and Beyond the Silent Cinema - Plebuch, Tobias (Journal of Film Music, 2013)
Musical topoi, such as religioso, battle, oriental etc., abound in generic silent film compositions (“photoplay music”) and catalogs of pieces for cinema musicians in the 1920s. As topoi are indeed useful to evoke meanings and to quickly produce a musical accompaniment for actions, they had been established in dramatic genres and program music long before film music became a profession after World War I. Misteriosos are a case in point to illustrate the formation and longevity of a musical topos from stage melodramas to sound films. When long feature films became mass entertainment and montage techniques advanced, cinema musicians had to develop new cataloging systems in order to gain control over a vast and rapidly growing repertoire of music suitable to accompany complex screen dramas at short notice. Accordingly, the catalogs grew increasingly complex and provided multidimensional taxonomies of nested categories by the end of the silent period.